Surface modification of biochar by using steam activation: article - Stephen Cornet, Cornelia Joyce; Jaapar, Jefri; Musa, Mohibah (2018)
Water pollution has been a major problem not only to the citizens but also the environment. In order to reduce water pollution and also other pollution, biochar had been choosen as an adsorbent. Surface modification by using steam activation had been performed in order to enhance the efficiency of removal of pollutants from water by increasing the surface area. The biochar undergoes pyrolysis process at a temperature 700°C before steam activation process. Steam activation at a temperature of 130°C for 30 minutes was found to be optimal in improving the surface of biochar as it shows greater surface area and high adsorption capacity. Although the temperature of 110°C produced higher fixed carbon and adsorption capacity, the differences were insignificant.